Low-Dose Intra-Arterial Urokinase and Aggressive Mechanical Clot Disruption for Acute Ischemic Stroke after Failure of Intravenous Thrombolysis - Yoon, W.; Park, M.S.; Cho, K.H. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Intravenous (IV) thrombolysis often fails to achieve recanalization of occluded cerebral arteries, especially in patients with proximal large arterial occlusions. The goal of this study was to assess the feasibility, safety, and efficacy of low-dose intra-arterial (IA) urokinase and aggressive mechanical clot disruption (AMCD) after failure of IV thrombolysis for acute ischemic stroke. MATERIALS AND METHODS: We prospectively enrolled 12 patients with acute ischemic stroke who initially received IV recombinant tissue plasminogen activator (rtPA) and were subsequently treated with combined low-dose IA urokinase and AMCD. Time to treatment, urokinase dose, duration of the procedure, recanalization rates, and symptomatic hemorrhage were analyzed. Clinical outcome measures were assessed on admission and at discharge (National Institutes of Health Stroke Scale [NIHSS]), and at 3 months after treatment (modified Rankin Scale [mRS]). RESULTS: Median NIHSS score on admission was 17. Median time from symptom onset to IV rtPA was 120 minutes, and median time from symptom onset to IA therapy was 230 minutes. The median duration of IA therapy was 55 minutes. Median dose of urokinase was 300,000 U. Recanalization (thrombolysis in cerebral ischemia grade II or III) was achieved in all patients. No procedure-related complications were observed. There was no symptomatic hemorrhage. At discharge, median NIHSS score was 3. The 3-month outcome was excellent (mRS, 0–1) in 8 patients, good (mRS, 2) in 1 patient, and poor (mRS, 3–5) in 3 patients. There was no hospital or 3-month mortality. CONCLUSIONS: In this study, combination therapy with low-dose IA urokinase and AMCD is safe and effective after failed IV thrombolysis in patients with acute ischemic stroke. A high rate of recanalization, low rate of symptomatic hemorrhage, and excellent functional outcome can be achieved.